The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1155/1994/60684
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Coherence Spectroscopy and Excited‐State Dynamics of Tolane and its Van Der Waals Complexes with Argon and Nitrogen

Abstract: We report the results of rotational coherence spectroscopy on tolane, tolane–Ar, and tolane–N2. The results on tolane are consistent with a planar geometry for the species. They also provide information about the symmetries of excited vibronic states in the species. The results on the van der Waals complexes provide significant experimental constraints on where the small species bind to tolane. In addition, we report the observation of a rapid excited-state decay process in the complexes and discuss the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…It is worth noting, that the first signatures of the post-pulse alignment were observed in birefringence of CS 2 vapor back in 1975 [514], furthermore, nonadiabatic excitation of rotational wavepackets had been widely used for rotational coherence spectroscopy [515]. However, the first experiment on nonadiabatic alignment of molecules in beams was performed in 2001 by Rosca-Pruna and Vrakking [516][517][518][519][520], who observed revivals of the alignment of I 2 and Br 2 molecules.…”
Section: Interaction With Short Laser Pulses: Nonadiabatic Alignment ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting, that the first signatures of the post-pulse alignment were observed in birefringence of CS 2 vapor back in 1975 [514], furthermore, nonadiabatic excitation of rotational wavepackets had been widely used for rotational coherence spectroscopy [515]. However, the first experiment on nonadiabatic alignment of molecules in beams was performed in 2001 by Rosca-Pruna and Vrakking [516][517][518][519][520], who observed revivals of the alignment of I 2 and Br 2 molecules.…”
Section: Interaction With Short Laser Pulses: Nonadiabatic Alignment ...mentioning
confidence: 99%
“…Averbukh and Arvieu [598] studied semiclassical catastrophes in the dynamics of a molecular rotor driven by a strong time-dependent field, and provided a recipe for the rotational squeezing by a sequence of laser pulses. Short-pulse rotational coherence spectroscopy can also be used to probe molecular structure, yielding information on molecular properties such as rotational constants and polarizabilities of large molecules and clusters, for both the ground and the electronically excited states [515,599,600]. Molecules interacting with short laser pulses can serve as a model to investigate nonlinear quantum phenomena in the dynamics of a kicked rotor, such as Anderson-like localization in angular momentum space [601].…”
Section: Interaction With Short Laser Pulses: Nonadiabatic Alignment ...mentioning
confidence: 99%
“…Diphenylacetylene (DPA; m = 1) and diphenylbutadiyne (DPB; m = 2) are attracting much attention as building blocks for dendrimers, electric molecular wires, molecular photonic devices, and two-photon absorption materials. Ground-state DPA has 1 A g symmetry in a planar D 2 h geometry. A number of spectroscopic studies on the electronically excited states of DPA have been carried out. The electronic structures within the Franck–Condon region under the D 2 h geometry have been identified. Okuyama et al reported the existence of three close electronic states for excitation in a supersonic jet and assigned the three states to 2 1 A g , 1 1 B 1u , and 1 1 B 2u states .…”
Section: Introductionmentioning
confidence: 99%